GROWTH, INTERMOULT PERIOD AND WEIGHT OF EDIBLE PORTIONS OF GIANT PRAWN AND TIGER SHRIMP - Darti Satyani (Research Center for Fisheries, 1996)
Since a prawn's body is covered by a hard cuticle, its growing mechanism develops through a moulting procese. The development of the adult giant prawn and tiger shri-p during the moulting cycles has been studied